HR Competency Development Trough Marketing Training for Tourism Operational Employees of Bumdes Sekapuk, Gresik - Eva Desembrianita; Anggardha Adi Septa; Muminatus Sholichah; Ulil Abshor Al Al Khikam (Kontribusia : Research Dissemination for Community Development, 2023)
The role of Human Resources in the organization can be seen from employees' contribution to the achievement of organizational performance. The growth in tourist arrivals from year to year is fully supported by the role of operational employee marketing competence in providing services to tourism consumers. Hence, increasing employee competence in marketing is a crucial thing Bumdes Sekapuk must do as the Setigi & KPI tourism business manager. University of Muhammadiyah Gresik lecturer community service conducts marketing training activities for Setigi & KPI operational employees as a Higher Education contribution to Tourism SMEs in Gresik. Face-to-face training and discussion methods are carried out interactively with participants to provide solutions to marketing problems in the field. Implementing employee training by increasing knowledge, insight, and competence in tourism marketing activities is expected to improve the performance of tourist visits to Setigi and Pak Inggi Gardens (KPI) tourist destinations, Sekapuk Gresik village. Keywords: Bumdes Sekapuk, Employee Training, Competence.